Psychological aspects of unemployment : attributions about the causes of success and failure in job seeking : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey Universit - Hesketh, Beryl Lilian (Massey University, 1982)
The validity of applying Kelley's covariation attribution model to understanding the perceived causes of success and failure of job seekers was tested on 168 psychology students using hypothetical case descriptions in a laboratory study. The same model was also tested on the self attributions of 82 newly registered unemployed in a field study. Results from the laboratory study provided support for Kelley's predictions for ability and luck attributions. Mixed support was obtained for task difficulty/ease attributions, partly because of the influence of order effects and the bias against attributing success to task ease. Little support was obtained for effort attributions, with only distinctiveness demonstrating the predicted significant main effect. In the field study, where self attributions were obtained for a previous success in job seeking and for currently being unemployed, support for Kelley's covariation model was weak with only distinctiveness relating significantly to lack of ability and consistency to bad luck. Possible reasons offered for the lack of support for the theory in the field study include the influence of group identity, individual differences in the perception of the stability and locus of causes, and the greater realism of the field setting. The fundamental attribution error and the success failure bias were tested in the laboratory setting for other attributions and in the field study for self attributions. More support was obtained for the predicted relationships involving attributions about others' behaviour in the laboratory study than for self attribution in the field study. For both self and other attribution, internal factors were stressed more than external factors. In the field study the combined influence of self-esteem and locus of control on the perceived causes for being unemployed was examined. Those with high self-esteem and an internal locus of control attributed success to ability and failure to lack of effort as predicted. Those with low self-esteem and an external locus of control did not attribute failure to lack of ability, but they did attribute success to unstable factors. Of the 82 unemployed, 51 were followed up one month later when 24 had jobs while 27 remained unemployed. Those with jobs had, at the first interview, made stronger task difficulty attributions for being unemployed and stronger effort attributions for a previous success than had those who remained unemployed. It appeared that the successful group externalised their difficulty while taking credit for success. In the group as a whole lower G.H.Q. scores (fewer negative mental health symptoms) were obtained among those who made strong lack of effort attributions for failure. The G.H.Q. correlated positively and significantly with the number of job interviews attended and with age. The dilemma of an active job search strategy which was associated with lower well-being as well as a greater likelihood of obtaining work is discussed. Supplementary analyses, including detailed case descriptions, were used to explore the relationship between personality variables, demographic variables, work importance and measures of well-being. Recommendations arising out of the research are offered and the importance of perceived skill level (distinctiveness) in influencing the extent to which blame attaches to the unemployed themselves for being out of work is stressed.
Keywords: Job seeking; Job seekers; Unemployed; Self-esteem; Attributions